Simultaneous removal of multiple heavy metals from soil by washing with citric acid and ferric chloride. Issue 13 (19th February 2020) - Shi, Jiyan; Pang, Jingli; Liu, Qinglin; Luo, Yating; Ye, Jien; Xu, Qiao; Long, Bibo; Ye, Binhui; Yuan, Xiaofeng
Abstract : Citric acid and ferric chloride exhibited synergistic effect on the removal of multiple heavy metals from soil. Abstract : The remediation of soil contaminated with multiple heavy metals is a matter of great concern due to its serious threat to the ecosystem and human health. Batch and slurry reactor soil washing experiments were conducted to explore the removal of Cd, Cr, Pb and Zn using 7 agents. Citric acid (CA) and ferric chloride (FeCl3 ) exhibited an obvious synergistic effect on the removal of heavy metals. Furthermore, the concentration of heavy metals in different soil particle size fractions was closely related to the soil element concentrations. Fine sand (0.05–0.25 mm) had a strong adsorption capacity for Cr and Pb because of the high Mn concentration. Notably, heavy metals in smaller-size soil particles could be efficiently removed by CA and FeCl3 . After remediation, the bioavailability of heavy metals in soil decreased. The potential ecological risk of heavy metals in soil reduced from an extremely high level to a low level. Moreover, some elements ( e.g. Al, Mn and Fe) and organic matter in soil were dissolved by CA and FeCl3, which accelerated the desorption of heavy metals from the soil. In a slurry reactor experiment, the removal efficiencies of Cd, Cr, Pb and Zn were 94.8%, 79.5%, 92.7% and 97.2%, respectively. The combination of CA and FeCl3 is a feasible practice to remediate soil contaminated by multiple heavy metals.